Improving sorting practices to accelerate the ecological transition and promote the circular economy in the healthcare system - MOBALIGH , Meriem; AIT BEN ALI , Smail (Revue Internationale des Sciences de Gestion, 2026)
This study aims to assess the impact of the quality of the sorting process and ongoing training on the generation and management of healthcare waste at Sidi Hssain Bennaceur Provincial Hospital Ouarzazate. The results demonstrate that over 60% of all waste produced is infectious healthcare waste, which is much higher than the national average. This inaccurate classification of infectious healthcare waste can be attributed to gaps in the sorting process resulting from a lack of healthcare waste management training (χ² = 7.24, p < 0.007). In conclusion, a waste reduction strategy based on rigorous improvements in waste sorting, ongoing staff training, the provision of appropriate equipment, and enhanced organizational coordination appears essential to ensuring staff safety, compliance with regulatory standards, and the sustainability of medical waste management within the hospital.